New synaptic and molecular targets for neuroprotection in Parkinson's disease. Issue 1 (23rd August 2012) - Calabresi, Paolo; Di, Massimiliano; Gallina, Antongiulio; Wang, Yingfei; Stankowski, Jeannette N.; Picconi, Barbara; Dawson, Valina L.; Dawson, Ted M.
<x xml:space="preserve">Abstract</x> The defining anatomical feature of Parkinson's disease (PD) is the degeneration of substantia nigra pars compacta (SNc) neurons, resulting in striatal dopamine (DA) deficiency and in the subsequent alteration of basal ganglia physiology. Treatments targeting the dopaminergic system alleviate PD symptoms but are not able to slow the neurodegenerative process that underlies PD progression. The nucleus striatum comprises a complex network of projecting neurons and interneurons that integrates different neural signals to modulate the activity of the basal ganglia circuitry. In this review we describe new potential molecular and synaptic striatal targets for the development of both symptomatic and neuroprotective strategies for PD. In particular, we focus on the interaction between adenosine A2A receptors and dopamine D2 receptors, on the role of a correct assembly of NMDA receptors, and on the sGC/cGMP/PKG pathway. Moreover, we also discuss the possibility to target the cell death program parthanatos and the kinase LRRK2 in order to develop new putative neuroprotective agents for PD acting on dopaminergic nigral neurons as well as on other basal ganglia structures. © 2013 Movement Disorder Society